METODE PENGEMBANGAN BAHASA: PENERAPANNYA PADA PEMBELAJARAN BERBASIS TEMA DAN SENTRA DI TAMAN KANAK-KANAK - Pudjaningsih, Wiwik (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
Purpose of writing of this article is explain "language expansion method and the applying at learning bases on theme and sentra in Nursery school". With respect to it, this article studies fundamental three things, that is language expansion method, learning in Nursery school, and language expansion method at learning in Nursery School. Solution firstly include; covers elementary development and child language indicator, expansion of child language competence, and ability expansion is having language through playing. Including second solution method to tell a story, speaks, question-answer, plays at role, sosiodrama, and fild trip. Solution third include; covers learningÂ in Nursery School and applying of language expansion method at learning in Nursery School. Keywords: method, language expansion, theme, area, Nursery School